The effect of intermittent vaccination of the beef cow herd on herd production - Marsh, Todd J. (Kansas State University, 2008)
Annual vaccination of the beef cow herd is a common management tool for most beef herd operations. However, no studies have established the minimal vaccination frequency needed to attain an acceptable herd production output with minimal financial inputs. The hypothesis of this study stated that the production output and profitability of the cow herd would not be decreased by vaccinating the cow herd at intervals of greater than one year. An animal's immune response to a vaccine or a direct challenge by a pathogen requires it to partition nutritional resources from other functioning biological systems within the body such as reproduction and lactation. According to the concept of diminishing returns, there is a point at which the cost of inputs (labor costs, vaccine costs and frequency of vaccination) does not result in corresponding levels of production output (measured by calf weaning weight, cow pregnancy rate and calf survivability). Thus, the objective of this thesis was to evaluate the effect of varying the interval of vaccination on cow reproductive productivity, calf productivity at weaning and herd profitability. It is important to note that this research study does not question the premises of vaccinating a cow herd or the effectiveness of the vaccines, but only investigates the time interval between vaccinations. This study consisted of approximately 1000 head of beef cattle divided between two ranch locations in south central South Dakota. Permanent and yearly production records were collected for each individual cow and calf for three production years 1998, 1999 and 2000. At each location cows were randomly assigned into four treatment groups:1) Group V0 – control or non-vaccinated, 2) Group V1 – vaccinated in 2000, 3) Group V2 – vaccinated in 1999 and 2000 and 4) Group V3 – vaccinated in 1998, 1999 and 2000. At the conclusion of this four year study, varying the interval of vaccinations did not decrease the production and the profitability of the treatment groups compared to the control group in the weaning weight and calf mortality models. However, in the pregnancy model conception rates were significantly reduced in 2 of the 3 treatment groups.
Keywords: Beef; Vaccination; Frequency; Pregnancy; Weaning Weights; Agriculture, Animal Culture and Nutrition (0475); Biology, Veterinary Science (0778); Economics, Agricultural (0503)